In-situ development of a functional prebiotic strawberry preparation - Gonçalves, Daniela Alexandra (2022)
Background Consumers are becoming more conscious about the foods they eat, particularly in terms of sugar and calorie content. In this vein, the food industry has been pressed to offer products with low-sugar and reduced caloric value. The main challenge is keeping rheological and sensory characteristics unchanged when removing or replacing those sugars [1]. Herein we developed a functional strawberry preparation for the dairy industry by enzymatic conversion of its sucrose content into prebiotic fructo-oligosaccharides (FOS). Commercial enzymatic complexes with transfructosylation activity were applied to catalyze the conversion using an in situ approach. Methodology Two enzymatic complexes, Pectinex® Ultra SP-L and Viscozyme® L, were tested for application in the strawberry preparation. Operational parameters, including temperature, pH and enzyme:substrate ratio (E:S), were optimized to maximize FOS yield. Rheological, and physicochemical properties of the enzymatic-treated strawberry preparation were analyzed. INFOGEST gastrointestinal digestion protocol was used for evaluating its functional properties [2]. Sugars were analyzed and quantified by HPLC [3]. Finally, the enzymatic reaction was scaled-up to a lab size bioreactor (1.5 L). Results and discussion The optimal conditions found for both enzyme complexes were 60 and pH 5.0. At this conditions, Pectinex® Ultra SP-L produced 265±3 g·L1 FOS, yielding 0.581±0.006 gFOS·gini.GF1 after 7 h reaction (E/S: 1/40); and Viscozyme® L produced 295±1 g·L1 FOS, yielding 0.664±0.004 gFOS·gini.GF1 after 5 h (E/S: 1/30). Both resulted in preparations with 50% (w/w) FOS, with the sucrose content reduced by <80%. The synthesized FOS showed resistance to gastrointestinal digestion; only kestose was slightly hydrolysed in the presence of gastric and intestinal fluid. The scaled-up fermentation yielded 0.62±0.02 g·gini.GF1, after 4 h reaction using Viscozyme® L, attaining a final FOS content of 281±7 g·L1 with 46% (w/w) FOS. Differences in water activity, ºBrix and consistency were not relevant, while colour had to be adjusted from browner to reddish and pH from 4.7 to 4.2. Conclusions A prebiotic strawberry preparation was successfully produced by enzymatic conversion of sucrose into functional prebiotics. The in situ fermentation proved to be efficient and suitable for industrial application.